2015
DOI: 10.3389/fphys.2015.00246
|View full text |Cite
|
Sign up to set email alerts
|

The implication of protein malnutrition on cardiovascular control systems in rats

Abstract: The malnutrition in early life is associated with metabolic changes and cardiovascular impairment in adulthood. Deficient protein intake-mediated hypertension has been observed in clinical and experimental studies. In rats, protein malnutrition also increases the blood pressure and enhances heart rate and sympathetic activity. In this review, we discuss the effects of post-weaning protein malnutrition on the resting mean arterial pressure and heart rate and their variabilities, cardiovascular reflexes sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 100 publications
(207 reference statements)
4
27
0
Order By: Relevance
“…Other experimental models of protein malnutrition, where offspring were subjected to protein deprivation following weaning, showed an evident BR dysfunction and establishment of hypertension. 31,32,41,42 This evidence supports the hypothesis that timing exposure is important to determine cardiovascular outcomes and suggests that a maternal diet poor in protein may induce adaptive mechanisms to protect the body from further damage, without affecting the development of the baroreceptors.…”
Section: Discussionsupporting
confidence: 71%
“…Other experimental models of protein malnutrition, where offspring were subjected to protein deprivation following weaning, showed an evident BR dysfunction and establishment of hypertension. 31,32,41,42 This evidence supports the hypothesis that timing exposure is important to determine cardiovascular outcomes and suggests that a maternal diet poor in protein may induce adaptive mechanisms to protect the body from further damage, without affecting the development of the baroreceptors.…”
Section: Discussionsupporting
confidence: 71%
“…First, animal experiments reveal that malnutrition in early life was associated with reconstruction of arterial wall and higher arterial stiffness and blood pressure in later life. 26,27 Similarly, people with in utero Abbreviations: CI = confidence interval; HR = hazard ratio; ICH = intracerebral hemorrhage. a Deep hematoma: basal, ganglia, thalami hematoma, cerebellar, and brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…Offspring of rats that were undernourished during the entire period of gestation and lactation showed raised catecholamine levels, an increase in catecholamine receptors and diminished cardiac beta-adrenergic responsiveness (12, 13). A review of studies of rats that were exposed to protein malnutrition in early life showed several effects on cardiovascular control systems, including increased sympathetic and decreased parasympathetic nervous system activity (14). There is also some evidence in humans that poor maternal nutritional status may impact sympathetic nervous system activity in the offspring, although the direction of the association is opposite to that demonstrated in most animal work.…”
Section: Introductionmentioning
confidence: 99%